Avaliação da correspondência de um procedimento de rastreio de função com uma análise funcional padrão: replicação de Slanzi et al - Barbosa, Rutelea dos Reis (2024)
The standard Functional Analysis is considered the gold standard procedure for identifying the function of problem behaviors and subsequent intervention. Various proposals have been used to reduce the time required to perform the standard functional analysis and the exposure of patients to reinforcement contingencies for problem behaviors. Slanzi et al. (2022) proposed a function screening procedure to identify whether problem behaviors are maintained by automatic reinforcement contingencies, socially mediated positive or negative reinforcement contingencies. The goal of this work was to replicate the proposal of Slanzi et al. (2022), comparing the results of the modified screening procedure with a standard functional analysis (cf. Iwata et al., 1982/1994) and identifying the degree of correspondence obtained. A secondary objective was to assess the social validity of the screening procedure by the therapists who conducted the procedure. Five participants who exhibited problem behaviors were selected. A screening analysis was conducted, as described by Slanzi et al. (2022), and a standard functional analysis, to compare the results with those of the screening procedure. A questionnaire assessed the social validity of the screening procedure with the therapists who implemented the procedure. A correspondence was identified in 80% of the participants between the results of the function screening procedure and the standard functional analysis. The social validity data indicated high satisfaction with the use of the procedure, and all therapists indicated that they would use the procedure in future evaluations. The data from the present study, by replicating the results of Slanzi et al. (2022), confirm the efficacy of the procedure and indicate a high degree of specificity and sensitivity of the procedure in identifying the function of behavior problems when compared to the results of the standard functional analysis